Body shape of patients with chromosomal aberration - Buday, József; Kaposi, Ilona (Acta Biologica Szegediensis, 2002)
The body shape of ten patients (4 with different forms of mucopolisaccharidosis, 2 with Cockayne syndrome and 1-1 with Klippel-Feil, Sturge-Weber, Rubinstein-Taybi and Cri du chat snydrome) are described in this study. Our aim is to call the attentiton to the importance of the detailed antropological examination of these patients, because this is one of the possible ways to understand how different genes influence of the shape of the body.